Special educational needs: a resource for practitioners - Farrell, Michael (London : Paul Chapman, 2004)
By examining related disciplines, Farrell provides a road map for special education and considers how special education can be better understood.
Includes bibliographical references and index.
BIED
Keywords: Special Education; Special education -- Great Britain; Special education; Special education; Great Britain